Revealing English Teachers’ Views of Digital Technology Integration at Vocational Universities - Pratiwi, Damar Isti; Waluyo, Budi (UNIB Press, 2024)
Previous research has validated teachers' positive attitudes toward incorporating digital technology into general English classes, but little research has been undertaken in vocational universities, where English is classified as English for Specific Purposes. As a response, this study explored vocational university teachers’ perceptions of integrating digital technology in teaching English by considering years of teaching experience. Framed by a mixed-method research design with surveys and interviews, it engaged 120 vocational university teachers in Indonesia. Quantitative data were examined using descriptive statistics, paired-sample t-tests, and one-way ANOVA, while thematic analysis was applied to qualitative data. The analysis showed that 66.5% teachers perceived advantageously toward digital technology integration in the teaching of English to vocational university students. The findings disclosed that most participants perceived digital technology integration positively in terms of helping teachers teach English, increasing teachers’ creativity, assisting students in learning English, and supporting teachers’ professional development. Yet, 25% of the participants stated they were neutral, while 8.5% disagreed with the majority. It might be caused by challenges that still arose during technology integration in EFL classes. Further, there were no significant differences in statistical analysis comparing the teachers’ perception based on teaching experience. Several suggestions for teachers, vocational institutions, and educational policymakers were presented to shed light on vocational teachers’ professional development, which could improve the vocational education system.